2023
DOI: 10.1001/jamanetworkopen.2023.22505
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bundled Hyperpolypharmacy Deprescribing Compared With Usual Care Among Older Adults

Abstract: ImportanceOlder patients using many prescription drugs (hyperpolypharmacy) may be at increased risk of adverse drug effects.ObjectiveTo test the effectiveness and safety of a quality intervention intended to reduce hyperpolypharmacy.Design, Setting, and ParticipantsThis randomized clinical trial allocated patients 76 years or older who used 10 or more prescription medications to a deprescribing intervention or to usual care (1:1 ratio) at an integrated health system with multiple preexisting deprescribing work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(158 reference statements)
1
3
0
Order By: Relevance
“…The Kaplan-Meier survival curve of the primary outcome revealed no trend suggesting a potential difference between groups toward the latter half of the 12-month period. This is in line with previous deprescribing studies with no demonstrable effects on clinical end points . There are several possible explanations why the intervention did not improve the primary end point.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Kaplan-Meier survival curve of the primary outcome revealed no trend suggesting a potential difference between groups toward the latter half of the 12-month period. This is in line with previous deprescribing studies with no demonstrable effects on clinical end points . There are several possible explanations why the intervention did not improve the primary end point.…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrated the safety of deprescribing in hospitalized patients with a high mortality rate in which more than 20% died during the 1-year follow-up. Mortality rates during the study period among previous studies ranged from 2.1% to 11.3% in the primary care setting, and from 5.6% at 90 days to 19.2% at 1 year in the inpatient setting, suggesting that our study population had a higher morbidity and mortality than previously reported studies. Our results corroborate the safety of deprescribing interventions in older inpatients with polypharmacy.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Over the past decade, multiple randomized controlled trials have tested interventions for deprescribing, including physician–pharmacist collaborative drug therapy management, mailing of educational brochure to patients and providers, and training sessions and family conferences for prescribers tailored for deprescribing. 18 , 19 , 20 Although some of these approaches have successfully reduced pill counts, further studies are needed to explore the effectiveness of these interventions in kidney care settings and on long-term outcomes (eg, hospitalizations, withdrawal events after deprescribing, ADE reduction, and patient-reported outcomes). As robust electronic platforms for deprescribing support are further developed, attention should also remain on tools that support effective shared decision making and patient-centered communication.…”
mentioning
confidence: 99%